La técnica básica del Parkour en la fuerza explosiva de tren inferior en adolescentes - Calderón Gavilanez, John Armando (2023)
The present research project is related to the development of lower body explosive strange in adolescents between 13 and 15 years of age; Its main objective is to investigate the impact of the training program based on basic parkour movements for the development of lower body explosive stregth. The working population was 13 adolescents using a simple sample of 7 male participants equivalent equivalent to 100%. Who are 13 to 15 years old. This research was based on quasi-experimental and field research with a cross-sectional and qualitative-quantitative character. The Abalakov test, which consist of a valuation table, was used as a research technique. The tabulation of data was carried out with the statistical program SPSS version 26 IBM. The result obtained was the basic Parkour training favors the development of lower body explosive strength with a degree of significance of 0.00 being less that 0.01 on the error scale, which is very significant result, so it is recommended to promote and encourage the practice of parkour in adolescents.